A COMPARATIVE STUDY OF PILE BEARING CAPACITY ANALYSIS RESULTS BASED ON THE EMPIRICAL METHOD (STANDARD PENETRATION TEST) AND THE FINITE ELEMENT METHOD (Jurnal Ilmiah Teknik Sipil, 2024)
This study aims to compare the bearing capacity of steel pile foundations using two approaches: an empirical method based on Standard Penetration Test (SPT) data with Meyerhof’s formula, and a numerical method based on the Finite Element Method (FEM). The research object is a steel pipe pile foundation with a diameter of 850 mm and a depth of 43 meters, used in a port dock structure. Data were obtained from field tests, including bore logs and corrected N-SPT values. The Meyerhof method was applied to manually calculate the end-bearing and shaft friction capacity of the pile, while the FEM approach involved two-dimensional geometric modeling using soil parameters derived from field data and technical assumptions. The analysis results indicate that the Meyerhof method yields an allowable bearing capacity of 7855.23 kN/m², whereas the FEM method results in a capacity of 1432.16 kN/m², with a comparison ratio of 0.1823. This discrepancy suggests that the finite element method provides more conservative and realistic results by thoroughly considering soil-structure interaction. Therefore, the finite element method is recommended for foundation design in large-scale projects or cases requiring high accuracy.
Keywords: Bearing capacity; finite element method; meyerhoff